Validity and reliability of the Thai functional internal rotation scale for shoulder arthroplasty - Nattha Kulkamthorn; Tharit Inkaratana; Pattanaket Cheewakongkiat (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2023)
Background: The Functional Internal Rotation Scale is an excellent clinical tool for evaluating patients with shoulder arthroplasty, but it has not been adapted to the Thai version. The objectives of this study were to translate the English version and culturally adapt the Functional Internal Rotation Scale to the Thai version and to examine the psychometric properties of the Thai Functional Internal Rotation Scale among Thai participants having shoulder arthroplasty. Methods: The Functional Internal Rotation Scale was translated to Thai, including cross-cultural adaptations, following standard guidelines. Psychometric properties were evaluated with shoulder arthroplasty patients. Content validity was evaluated using the content validity index (CVI). Criterion validity was assessed using the Pearson correlation coefficient. An Independent t-test was used to evaluate construct validity. Internal consistency reliability was assessed using Cronbach's alpha coefficient. Intraclass correlation coefficient (ICC) was used to determine test-retest reliability over a 14-day interval. Results: Of 45 participants, 20 total shoulder arthroplasty (TSA) patients and 25 reverse shoulder arthroplasty (RSA) patients, the majority of participants were female (69%) and retired (91%) with a mean age of 72.9 years (SD 9.1). CVI evaluation was acceptable, with a total CVI of 0.92. The correlation of the Thai Functional Internal Rotation Scale with the Thai version of the American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form (Thai ASES) and the internal rotation subscale (IR subscale) of the Thai ASES was 0.73 (P < 0.001) and 0.75 (P < 0.001), respectively. For construct validity, TSA patients scored, on average, 10.8 points higher than RSA patients (43.7 vs. 32.9, P < 0.001, 95% confidence interval 6.3–15.3). Cronbach's alpha coefficient of the Thai Functional Internal Rotation Scale was 0.95. The test-retest reliability revealed excellent reliability (ICC 0.99). Conclusion: The Thai Functional Internal Rotation Scale has good validity and excellent reliability in assessing internal rotation function in Thai shoulder arthroplasty patients.